Optimizing Vermicomposting of Coffee and Tea Wastes Using the Indian Earthworm Lampito mauritii: A Sustainable Waste Management Approach - Kavitha, V.; Anandhan, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The rapid generation of coffee and tea ground wastes poses significant environmental challenges, particularly in urban areas. This study evaluates the potential of the Indian earthworm Lampito mauritii to vermicompost these wastes, aiming to identify optimal substrate ratios for maximizing compost quality and plant growth. Five treatments combining soil substrate with coffee and tea wastes in 3:1 and 1:1 ratios were tested. Results showed that the 1:1 ratios of coffee (T2) and tea (T4) wastes significantly enhanced biomass (52.43 g/kg for T2) and hatchling production (58 in T2). Vermicompost from these treatments exhibited enriched macronutrient levels (nitrogen 20.1 g/kg, phosphorous8.4 g/kg, potassium 19.7 g/kg in T2) and boosted rose plant growth, with plants in T2 growing to 110 cm and producing 7 flowers. This study highlights vermicomposting as an efficient, low-cost method for organic waste recycling and sustainable agriculture.